An Evaluation of the Confinement provided by PVC and Cardboard Pipes in unconfined detonation velocity measurements - Thomas, Tiju John (My University, 2006)
African Explosives Limited (AEL) is involved with the Hybrid Stress Blast Model (HSBM) project in the characterisation of its bulk explosives and part of this involves the collection of unconfined detonation velocities (VoD). Historical methods of unconfined VoD measurements and earlier measurements taken for the HSBM project did not attribute significance to the strength of the light containment media used, which was either cardboard or PVC, in various wall thicknesses. The main focus of this exercise was to investigate this significance and to make recomendations to the HSBM on the choice of pipes for future tests. ANFO was used in order to avoid complexities of manufacturing and density variation, which arise with emulsion explosives. Plastic sleeves were used as a control in defining a medium of negligible confinement in order to compare the results in PVC and cardboard pipes. The cardboard pipes selected had wall thicknesses of 2mm and 4mm, while the PVC pipes had pressure ratings of 4 Bar and 9 Bar with wall thicknesses from 1.5mm to 8.5mm. The inner diameters ranged between 45mm and 253mm. The following findings have been made in this report. - Plastic sleeves were not effective in comparing the effects of confinement, but the results suggests that thin walled carboard pipes are probably very close to unconfined, even near the critical diameter. - PVC pipes affect VoD more than cardboard pipes and the confinement provided by both types of pipes increases with their wall thickness. - Critical diameter increases with weaker confinement and vice versa. - VoDs in the different types of confinement converge as diameter increases. - Future unconfined VoD tests should take cognisance of the findings of this project. A similar confinement investigation would be benificial to determine whether similar trends prevail with Emulsion and Emulsion-ANFO blend explosives. However if such an evaluation is not conducted, the minimum requirements for further tests should be to apply the confinement and diameter relationships as determined for ANFO during this investigation.
Student Number : 9104308Y - Msc Eng research report - School of Mining Engineering - Faculty of Engineering and the Built Environment
Keywords: unconfined velocity of detonation; VOD; PVC; cardboard; ANFO; light confinement; media; critical diameter